Kompetensi Pedagogik Guru, Model Discovery Learning, dan Gaya Belajar terhadap Kemandirian Belajar - Lilik Istianingsih Hermawati; Endah Andayani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
Abstract Teachers become the most important determinants of school-based classes that play a role in improving student learning outcomes because they interact directly with students while in school. The objectives of this study are: (1) to determine the effect of teacher pedagogical competence, discovery learning models, and learning styles on student learning independence, (2) to determine the effect of teacher pedogogical competence on student learning independence, (3) to determine the effect of discovery learning models on student learning independence, and (4) to determine the effect of learning styles on student learning independence. This research also includes correlational research. The study population was all High Class students from elementary schools in Guslah II, Lekok District, Pasuruan Regency, in the odd semester, 2019/2020 school year, totaling 256 students. While the sample is 25% of the population (64 students). Data collection methods by questionnaire and observation. The results showed: (1) simultaneous teacher pedogogical competence, discovery learning models, and learning styles affect the independence of student learning. (2) the pedogogical competence of teachers influences the learning independence of students (3) the discovery learning model influences the learning independence of students, and (4) learning styles affect the independence of student learning